Widespread variability in overnight patterns of ecosystem respiration linked to gradients in dissolved organic matter, residence time, and productivity in a global set of lakes. (30th August 2014) - Sadro, Steven; Holtgrieve, Gordon W.; Solomon, Christopher T.; Koch, Gregory R.
Abstract : We characterized patterns of nighttime ecosystem respiration (ER) in 23 globally‐distributed lakes using free‐water changes in dissolved oxygen (DO). We considered three alternative models of ER to describe overnight changes in DO: constant ER, linearly declining ER, or logistically declining ER. Variation in ER was widespread. Each model of respiration was found to best fit observed overnight DO dynamics with some degree of frequency in every lake. Constant ER occurred with an average frequency of 62% across lakes and was most commonly the best description of DO dynamics. It never occurred with a frequency < 19% in any lake and ranged up to 90% in one dystrophic lake. The average frequency across lakes with which the linear and logistic models occurred was 21% and 17%, respectively, although they ranged as low as 3% and as high as 42% in some lakes. Although data limitations restricted the majority of our analysis to summer months, annual data records from five lakes suggest there is little seasonal variation in the frequency with which patterns occurred. As our conceptual model predicted, the frequency of constant ER among lakes increased and logistic ER decreased along a gradient of increasing terrestrial influence. However, despite significant correlations with total phosphorus and photosynthetically active radiation, the effect of lake productivity on the frequency of patterns of ER among lakes was less clear. This study suggests that diel variability in ER results from complex interactions between different components of respiration and the forcing factors that govern them.